A redefinition of Gauromaia Pascoe, 1866 (Coleoptera: Tenebrionidae: Stenochiinae) - Telnov, Dmitry; Ruzzier, Enrico (Zootaxa, 2024)
Gauromaia dives Pascoe, 1866, type species of the genus, is redescribed; Celebesa Pic, 1921, hitherto a genus in Cnodalonini Oken, 1843, is downgraded in rank to a subgenus of Gauromaia Pascoe, 1866. The subgeneric rank is confirmed for Gauromaia (Falsogauromaia Pic, 1921). The following new combinations are proposed: G. (Celebesa) elongata (Pic, 1921) comb. nov., G. (C.) impressa (Pic, 1923) comb. nov., G. (C.) latipennis (Pic, 1921) comb. nov., G. (C.) striata (Pic, 1923) comb. nov., and the synonym Celebesa purpurea (Pic, 1921) syn. nov. is introduced for Gauromaia (Celebesa) angustior (Pic, 1921) comb. nov. Lectotype designations are made for five species: Gauromaia dives, Gauromaia (Celebesa) angustior, Gauromaia (Celebesa) purpurea, Gauromaia (Celebesa) elongata, and Gauromaia (Falsogauromaia) annulipes Pic, 1921. An annotated checklist of Gauromaia species, a key to its subgenera, and a key to the species of the subgenus Celebesa are presented for the first time. New faunistic records of Gauromaia (Celebesa) and G. (Falsogauromaia) are provided.